The influence of psychosocial factors on entrepreneurial intention among IKBN students - Nor Hanis, Mat Salleh (2015)
This study intends to examine the influence of psychosocial factors (college experience, social support and risk taking propensity) on entrepreneurial intention among IKBN students. The study was conducted using a questionnaire that was distributed to 365 students of IKBN Kuala Perlis. The data obtained from this survey was analysed using the Statistical Package for Social Science (SPSS) 20.0. The descriptive analysis was used to identify the profile of the IKBN Kuala Perlis' students. This study uses probability sampling design that apply unrestricted or simple random sampling where the element of population was known and every element has an equal or non-zero chance of being selected as sample subject. The results of correlation analysis showed that all psychosocial factors such as college experience, social support and risk taking propensity have significant and positive relationships towards entrepreneurial intention. While through regression analysis it proved that, all these variables are significantly influence the entrepreneurial intention among skillsbased students. This study helps many parties to realize that skills-based students as well have potential to be entrepreneurs. Thus, supports from various parties such NGOs and government is hope in order to help them to become successful entrepreneurs in the future